A single stone - McKinlay, Megan (Candlewick Press, 2017)
In a dystopian world, fourteen-year-old Jena has spent her entire life preparing for her role in her community as the leader of the tunnelers--seven girls chosen at birth due to their small size to squeeze through the small crevices of the nearby mountain to harvest the mica their village needs to survive. The girls spend their lives deprived of food, and their limbs are wrapped to decrease growth. It is a revered but difficult life. When Jena meets Lia, a girl from a village on the other side of the mountain who lives a more peaceful existence, both girls question everything they've ever been told.